Efficient gap repair in Drosophila melanogaster requires a maximum of 31 nucleotides of homologous sequence at the searching ends. - Keeler, K.J.; Gloor, G.B. (Molecular and Cellular Biology, 1997)
Double-strand breaks (DSB) were generated in the Drosophila melanogaster white gene by excision of the P-w(hd) element. An ectopic P-element vector carrying a modified white gene was used as a template for DSB repair. All template-dependent repair events were examined, and four different classes of events were recovered. The two most common products observed were gene conversions external to the P-w(hd) element and gene conversions (targeted transpositions) internal to the P-w(hd) element. These two events were equally frequent. Similar numbers for both orientations of internal conversion events were recovered. The results suggest that P-element excision occurs by a staggered cut that leaves behind at least 33 nucleotides of single-stranded sequence. Our results further demonstrate that an efficient homology search is conducted by the broken end with less than 31 nucleotides.